DNA Fragments Assembly Based on Nicking Enzyme System - Wang, Rui-Yan; Shi, Zhen-Yu; Guo, Ying-Ying; Chen, Jin-Chun; Chen, Guo-Qiang (PLOS ONE, 2013)
A couple of DNA ligation-independent cloning (LIC) methods have been reported to meet various requirements in metabolic engineering and synthetic biology. The principle of LIC is the assembly of multiple overlapping DNA fragments by single-stranded (ss) DNA overlaps annealing. Here we present a method to generate single-stranded DNA overlaps based on Nicking Endonucleases (NEases) for LIC, the method was termed NE-LIC. Factors related to cloning efficiency were optimized in this study. This NE-LIC allows generating 3′-end or 5′-end ss DNA overlaps of various lengths for fragments assembly. We demonstrated that the 10 bp/15 bp overlaps had the highest DNA fragments assembling efficiency, while 5 bp/10 bp overlaps showed the highest efficiency when T4 DNA ligase was added. Its advantage over Sequence and Ligation Independent Cloning (SLIC) and Uracil-Specific Excision Reagent (USER) was obvious. The mechanism can be applied to many other LIC strategies. Finally, the NEases based LIC (NE-LIC) was successfully applied to assemble a pathway of six gene fragments responsible for synthesizing microbial poly-3-hydroxybutyrate (PHB).